Pterygium Is a Pre-Malignant Condition: A Systematic Review: Pterygium: A Pre-Malignant Condition - Khan, Muhammad Saeed Zafar; Malik, Abdul Majeed; Ahmed, Chaudry Nasir; Chachar, Aijaz Zeeshan Khan; Saeed, Amina; Akram, Gulbano (Pakistan Journal of Health Sciences, 2025)
In a hot and humid climate Pterygium is one of the common ocular surface disorders. The ultraviolet radiations have been implicated in the pathogenesis of this condition. Objectives: To investigate the association between pterygium and ocular surface squamous neoplasia (OSSN) and to determine the prevalence rates of both diseases in varied populations worldwide. Methods: The internet search in the selected databases resulted in 420 articles in the first round. The second round of screening of the titles excluded 26 articles ascribed to be duplicates. The third round of evaluation ended with the exclusion of 341 articles because they lacked an association between the pterygium and OSSN. In the final round, 29 studies were excluded according to the inclusion and exclusion criteria. Results: A total of 12492 pterygia samples were reported in 24 studies. Most of the studies had been conducted in hot and temperate climates. Out of these twenty-four, three studies were from areas of low UV Radiation like Canada, while six were from the USA, three were from South America, four studies were from Australia and New Zealand, three were from Europe, and one each was from South East Asia, the Middle East, and Far East Asia and Africa. Conclusions: There is a paucity of homogeneity in the reported data on the correlation of pterygium and OSSN. Such studies will delineate the relationship between patients with pterygium and suspected OSSN and will provide predictive information to care for public health issues in these countries.